The Dual Power of Silence: Revering God and Rejecting Idols in Habakkuk and Gregory of Nyssa - Suwanto, Wilson W. (Theological Journal Kerugma, 2025)
This study examines the dual role of silence as reverence for the divine and rejection of idolatry in the Book of Habakkuk and the works of Gregory of Nyssa. Through qualitative textual analysis and comparative study, it explores how these figures, separated by centuries and traditions, converge in their understanding of silence as a response to divine mystery. The research reveals that both Habakkuk and Gregory view silence as an acknowledgment of human limitations in comprehending the divine and as a safeguard against idolatry. Their insights remain relevant in addressing contemporary spiritual challenges, offering a counterpoint to modern tendencies of excessive verbalization and intellectual control in religious practice. This study contributes to a deeper understanding of silence in Judeo-Christian thought and its potential applications in contemporary spirituality.